2012
DOI: 10.1007/s11999-012-2331-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Three-dimensional CT Predicts Intraoperative Findings in Hip Arthroscopy

Abstract: Background Currently, plain radiographs and MRI are the standard imaging modalities used for diagnosing femoroacetabular impingement (FAI) and preoperative planning for arthroscopic treatment of FAI. The value of three-dimensional (3D) CT for these purposes is unclear. Questions/purposes We therefore determined the reliability of CT assessment of FAI and whether CT findings of hip disease predict arthroscopic findings. Methods We retrospectively assessed the preoperative CT scans of 118 patients who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 38 publications
1
64
0
Order By: Relevance
“…Up to 50% of crossover signs indicating acetabular retroversion on plain AP radiographs have shown not to be present on 3D CT scans [36]. Intraoperative findings of labral damage have been positively correlated with preoperative alpha angles measured on 3D CT scans, which is consistent with our study [14]. Konan found the frog lateral plain radiograph to significantly underestimate the alpha angle when compared to 3D CT scans [19].…”
Section: Discussionsupporting
confidence: 88%
“…Up to 50% of crossover signs indicating acetabular retroversion on plain AP radiographs have shown not to be present on 3D CT scans [36]. Intraoperative findings of labral damage have been positively correlated with preoperative alpha angles measured on 3D CT scans, which is consistent with our study [14]. Konan found the frog lateral plain radiograph to significantly underestimate the alpha angle when compared to 3D CT scans [19].…”
Section: Discussionsupporting
confidence: 88%
“…Kitadai et al [15] compared LCEA measurement to the Visser method and found no difference at different SCFE severity levels, concluding LCEA can be accurately measured in a hip with SCFE. Interobserver variability ICCs reported in the literature are 0.83 for AV sup [6], 0.69 for AV cen [11], and 0.78 for LCEA [11] measured on CT. We used Levene's test to determine equality of variances among the three groups at both measurement locations. One-way ANOVA was used to identify differences in acetabular version among the three groups at both measurement locations.…”
Section: Methodsmentioning
confidence: 91%
“…Abnormalities of morphologic features that can lead to FAI include cam abnormality on the femoral side and/or pincer overcoverage on the acetabular side [15,33]. Normal parameters for both of these have been defined for plain radiography and advanced imaging [2,5,7,14,19,29,35,37,41]. The alpha angle, Each author certifies that he or she has no commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements, etc) that might pose a conflict of interest in connection with the submitted article.…”
Section: Introductionmentioning
confidence: 99%
“…initially described by Notzli et al [25] and validated on axial oblique images of MRI [25] (and subsequently CT [14]), has recently emerged as a method of quantifying the cam lesion. The lack of universal availability of MRI and potential uncertain risks of radiation from CT have been limitations with these imaging modalities, forcing exploration of the measurement methods with biplanar radiographs [2,11,23,35] to ensure wider applicability for screening [12,34].…”
Section: Introductionmentioning
confidence: 99%